Pengaruh Pendapatan Asli Daerah (PAD), Belanja Modal dan Dana Alokasi Umum terhadap Pertumbuhan Ekonomi di Provinsi Jawa Tengah Tahun 2022–2024 - Ammar Muhammad Zain; Henryanto Wijaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of Regional Original Revenue (PAD), Capital Expenditure, and General Allocation Fund (DAU) on Economic Growth in Central Java Province during 2022–2024. The research applies a quantitative approach with panel data regression and associative analysis. The data used are secondary data obtained from the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance and the Central Bureau of Statistics (BPS) of Central Java Province. The sample includes 35 regencies and cities observed over three years. The results show that PAD has a positive and significant effect on economic growth, indicating that higher fiscal independence can stimulate regional economic activity. Capital expenditure also has a positive influence, emphasizing the importance of local government investment in productive sectors such as infrastructure and public services. Meanwhile, the General Allocation Fund (DAU) shows a positive but varying effect across regions, depending on management efficiency and allocation effectiveness. Overall, the study highlights that the synergy among PAD, capital expenditure, and DAU plays a crucial role in strengthening regional fiscal capacity to achieve sustainable economic growth in Central Java Province. Keywords: Regional Original Revenue; Capital Expenditure; General Allocation Fund; Economic Growth; Central Java